PERAN IBU DI JAWA - Harjito . (Universitas PGRI Semarang, 2014)
This paper aims to describe the relationship and the role of mother to child inJava. Subject of the study consisted of two stories. The method used is the analysis ofthe text. Relationship is the relationship between mother and child, both biologicalchildren or not. In relation, the mother role to protect their children, whether they arefemale or male. In relation mother and boys, women contribute to protect him. Thisalso denies the stereotype that men always protect women.keywords: relationship, mother, child, protect.